Makna Kerja Ibadah (Studi Pada Perusahaan Kalla Group di Makassar) - Syamsuddin Syamsuddin; Muhammad Wahyuddin Abdullah (AkMen JURNAL ILMIAH, 2020)
The main problem in this study is what is the meaning of the work of worship in the Kalla Groupcompany in Makassar. The subject matter is then reduced to how it is implemented in its activities at thecompany.This type of research is qualitative with the research approach used is a case study. The datacollection techniques in this research are through observation, study of literature and interviews. Dataprocessing and analysis techniques are carried out through data reduction, data presentation andconclusion drawing.The results of this study indicate that there are 5 (five) values contained in worship work at KallaGroup companies, namely Tawheed, Ikhlas, Amanah, Honest and Istiqomah. This value is implemented incorporate activities both in the magdah and ghair magdah worship.The implications in this study are: 1) Work of worship is one of the guidelines in the religion ofIslam because it is a command especially to men who have a family to support their family life inmaintaining survival. So that work is not just work, it needs to be accompanied by God's involvement inall activities so that it is worth worshiping. 2) Understanding of the work of worship will lead toemployees that by working as well as a place to pile the reward fields in order to get the Grace fromAllah SWT.